The Church and Northern English Society in the Fourteenth Century : The Archbishops of York and Their Records. - Dryburgh, Paul (York Medieval Press, 2024)
Insights into ecclesiastical, political, cultural and social history of the north of England through an exploration of the administrative archives of fourteenth century archbishops.
Keywords: Catholic Church. -- Province of York (England) -- History -- 14th century.; Christianity and culture -- History -- Middle Ages, 600-1500.; Christianity and culture -- England -- History.; York (England) -- Church history -- 14th century.; Great Britain -- History -- 14th century.; Grande-Bretagne -- Histoire -- 14e siècle.; Christianisme et civilisation -- Angleterre -- Histoire.; HISTORY / Europe / Great Britain / Norman Conquest to Late Medieval (1066-1485).; Alexander Neville.; Apostasy.; Archbishop Richard Scrope.; Archbishop William Greenfield.; Archbishop William Melton.; Carlisle.; Clerical Taxation.; Durham.; Edward II.; Edward III.; Excommunication.; Henry IV.; John Thoresby.; Pilgrimage.; Robert Waldby.; Thomas Arundel.; Thomas, earl of Lancaster.; William Zouche.